Characterization and transcriptomic analysis of a native fungal pathogen against the rice pest Nilaparvata lugens - Wang, Zheng-Liang; Wang, Yan-Dan; Cheng, Yi-Qing; Ye, Zi-Hong; Liu, Guang-Fu; Yu, Xiao-Ping (Frontiers in Microbiology, 2023)
The brown planthopper (BPH), Nilaparvata lugens, is one of the most destructive pests of rice. Given the threats posed by insecticide resistance to its control, eco-friendly strategies based on microbial pathogens emerged as a promising biocontrol alternative. In the present study, we isolated a native fungal pathogen against BPH from infected BPH cadavers and preliminarily identified as a strain of Aspergillus fumigatus based on morphological and molecular methods. Laboratory bioassay revealed that this fungal strain was highly virulent to BPH both at nymphal and adult stages, with the median lethal times (LT50) of 7.5 and 5.8 days under high conidial concentration of 1 × 109 conidia mL–1. A genome-wide view of gene expressions in BPH against fungal attack was analyzed by transcriptomic sequencing and consequently a large number of differentially expressed genes that mainly involved in host immune defense and cell detoxification were found. RNAi-mediated knockdown of an upregulated gene encoding a serine protease (NlSPN) could cause a significant decrease in BPH survival. Combination of dsRNA injection and fungal infection showed an additive effect on BPH mortality, which provided clues to develop new pest management strategies against BPH.